Aspirations and women’s empowerment: Evidence from Kyrgyzstan - Kosec, Katrina; Akramov, Kamiljon T.; Mirkasimov, Bakhrom; Song, Jie (International Food Policy Research Institute, 2018)
Can having higher aspirations, or goals for the future, contribute to the empowerment of women? A growing literature shows that aspirations increase a host of forward-looking economic and political behaviors, from entrepreneurship to civic engagement. This has stimulated interest in development interventions aimed at reducing behavioral poverty traps. At the same time, a wealth of literature suggests that women’s empowerment and involvement in decision-making can be welfare-improving. It can increase household income and asset wealth by ensuring that women are economically active and have high levels of human capital; increase technical efficiency on the farm; and improve health, nutrition, and education outcomes for children. Linking these two literatures, we posit that one route to women’s empowerment may be to raise aspirations—either those of a woman herself, or those of her husband, who often wields considerable influence over her decision-making authority and access to resources. We find that having a husband who sets ambitious goals for himself predicts more egalitarian gender attitudes for both the husband and his wife. Higher aspirations on the part of wives also predict more egalitarian gender attitudes (for both the husband and his wife), but they additionally predict greater involvement of women in household decision-making. This suggests that efforts to fuel either men’s or women’s ambition can shift gender attitudes, but that targeting women is the more effective way to build women’s decision-making power.